Vocal signals of ontogeny and fledging in nestling black-cockatoos: Implications for monitoring. Issue 4 (4th July 2022) - Teixeira, Daniella; Hill, Richard; Barth, Michael; Maron, Martine; van Rensburg, Berndt J.
ABSTRACT: Bioacoustics offers new ways to monitor wildlife populations. Understanding vocal changes related to age can provide demographic data that are valuable but difficult to collect for threatened species. Here, we present the vocal signals of ontogeny and fledging in nestlings for two endangered black-cockatoos, the Kangaroo Island glossy black-cockatoo, Calyptorhynchus lathami halmaturinus, and the south-eastern red-tailed black-cockatoo, C. banksii graptogyne . Using sound recordings taken at wild nests ( n = 3 for the red-tailed black-cockatoo; n = 7 for the glossy black-cockatoo), we examined changes in nestling vocalisations through to fledging. Nestlings vocalised from 4 weeks of age, but calls were soft and infrequent until about 6 weeks. Daily call rate increased significantly in the final week of nesting. Peak amplitude increased significantly with development for both subspecies. Call duration increased significantly for the glossy black-cockatoo. Likewise, low frequency increased significantly for the glossy black-cockatoo. Average entropy decreased significantly for both subspecies. Aggregate entropy decreased significantly for the red-tailed black-cockatoo. Fledging was associated with a loud and distinct vocal event. Together, these changes in call rate and structure, and the presence or absence of fledging vocalisations, provide useful ways to broadly categorise nest age and determine nest outcome from sound recordings.